2021
DOI: 10.3390/brainsci11080984
|View full text |Cite
|
Sign up to set email alerts
|

Neural Circuits, Microtubule Processing, Brain’s Electromagnetic Field—Components of Self-Awareness

Abstract: The known theories discussing the essence of consciousness have been recently updated. This prompts an attempt to integrate these explanations concerning several distinct components of the consciousness phenomenon such as the ego, and qualia perceptions. Therefore, it is useful to consider the latest publications on the ‘Orch OR’ and ‘cemi’ theories, which assume that quantum processing occurs in microtubules and that the brain’s endogenous electromagnetic field is important. The authors combine these explanat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 73 publications
(109 reference statements)
0
10
0
Order By: Relevance
“…The idea that electromagnetic resonance is the fundamental mechanism of communications among molecules was first proposed by Veljkovic et al, who also suggested that such a mechanism could provide a long-range effective communication [187]. At this stage, we believe that a unification of the EMF and Orch OR theories of brain dynamics is conceptually very probable [156].…”
Section: Penrose and Hameroff's Orch Ormentioning
confidence: 76%
See 1 more Smart Citation
“…The idea that electromagnetic resonance is the fundamental mechanism of communications among molecules was first proposed by Veljkovic et al, who also suggested that such a mechanism could provide a long-range effective communication [187]. At this stage, we believe that a unification of the EMF and Orch OR theories of brain dynamics is conceptually very probable [156].…”
Section: Penrose and Hameroff's Orch Ormentioning
confidence: 76%
“…Nevertheless, our analysis below can elucidate the fundamental quantum coherent properties of the microscopic EM fields invoked by such an approach. [150][151][152][153][154][155][156].…”
Section: Electromagnetic Fields In the Brainmentioning
confidence: 99%
“…At this stage, we believe that a unification of the EMF and Orch OR theories of brain dynamics is conceptually very probable [94].…”
Section: Penrose and Hameroff's Orch Ormentioning
confidence: 90%
“…Although the TDCS-induced physiological mechanisms are not yet fully understood, it is assumed that its effects are based on long-term potentiation (LTP) and longterm depression-like (LTD) mechanisms [88,89]. Although the EMF approach was not originally related to QM when it was first formulated [9][10][11][12][13][14][15][16][17], a deeper quantum optical reformulation [90][91][92][93][94] cannot be excluded in principle.…”
Section: Electromagnetic Fields In the Brainmentioning
confidence: 99%
See 1 more Smart Citation